Sosialisasi Pencegahan Child Grooming pada Siswa Kelas V dan VI SDN 1 Ngadisuko - Aditya Pinda Kusuma; Muflihatul Bariroh; Ahmad Fahrudin (Kerigan: Jurnal Pengabdian Masyarakat, 2024)
Purpose: This community service activity aims to enhance elementary students’ understanding of the dangers of child grooming and equip them with basic self-protection skills, particularly in recognizing and resisting social manipulation that may occur both directly and through digital media. This issue is crucial because elementary school students are a vulnerable group who often lack awareness of potential threats in social relationships. Method: The program was conducted using an educational–participatory approach based on the Community-Based Research (CBR) model, involving fifth- and sixth-grade students of SDN 1 Ngadisuko, Durenan District, Trenggalek Regency. The activities consisted of two sessions of socialization using visual media, interactive discussions, quizzes, and simulation practices. Evaluation was carried out qualitatively through participatory observation and student reflections at the end of the sessions. Practical Applications: Through this socialization, students gained knowledge about the concept of child grooming, its various forms, and practical preventive measures. The activity also encouraged schools to foster openness in discussing child protection issues and consider integrating similar materials into their curriculum and extracurricular programs. Conclusion: The results indicate that students became more aware and prepared to respond to suspicious situations, both online and offline. This program serves as a strategic initial effort to build children’s self-protection awareness while strengthening the school’s role as the frontline institution for education-based child protection.